(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
With constant development and improvement of management systems in modern technological processes, in cars, in production lines and machinery and other fields are increasingly entering the use of different sensors. These sensors are tested on special test simulators, simulating the conditions for a long time close to their work. Often the temperature is in the range of 700-900°C. To achieve these temperatures, most environmentally safe and effective heating of the sensors can be achieved by induction heating of housing them. The object of this report is installation for induction heating system as part of the simulator to test the vibration and temperature thermal sensors.